Shaping multilateral trade: The changing institutional landscape - Peralta, Gloria Abraham; Campos Azofeifa, Adriana (International Food Policy Research Institute, 2024)
This chapter highlights the fact that many international trade stakeholders agree on the urgent need to strengthen the multilateral trade system and its governing body, the World Trade Organization (WTO). This will mean that the WTO will need to strengthen its intrinsic negotiating function, in particular its ability to achieve results in different processes in the trade agenda, and particularly in the negotiations on agriculture. Indeed, it has failed to completely fulfill its mandate to deepen the reform process, through the adoption of key disciplines in the major negotiation pillars, among them, domestic support, export restrictions and the search for innovative options to fulfill the Bali mandate on the establishment of public entities to promote food security. Moreover, negotiations on other issues that are relevant to a significant group of countries, such as market access, are moving at their own pace.